Pengaruh Kualitas Pelayanan Kepuasan Pelanggan Terhadap Loyalitas Nasabah (Studi Kasus Di Bank Bri Surakarta ) - DEWI, ARISTA; , Drs. Sri Padmantyo, M.B.A (2017)
The purpose of this study is to determine the effect of service quality and customer satisfaction to customer loyalty. This study used a sample of 150 respondents and the sample collection method using accidental sampling. The analytical tool used is multiple linear regression analysis T test analysis results obtained are quality of service and customer satisfaction to customer loyalty individually and F test results indicate the quality of service and customer satisfaction to customer loyalty. Implications of the study are expected to pay attention that prodheers should the quality of service by improving the quality of physical evidence, empathy, reliability, responsiveness and assurance, as well as improve customer satisfaction in terms of product quality and guarantee of product usage.